Digital Competence Among the Key Components of Future Masters of Primary Education Professional Training: Theoretical Interpretations - Oleksandr Blyznyuk; Tetiana Hotsaniuk (Vasyl Stefanyk Precarpathian National University, 2024)
The article draws attention to the issue of professional training of future masters of primary education and the role of digital competence in it. It involves addressing various challenges and considerations to ensure that educators are well-equipped to meet the diverse needs of primary school students. The author outlines several aspects in this direction: innovative pedagogical knowledge and skills, active technology integration, proper classroom management, appropriate assessment and evaluation, and professional development. It is proved that integration of technology into the classroom results in digital competence improvement of future educators. Numerous interpretations of digital competence by Ukrainian and foreign researchers are presented. The international scientific findings proved, the concept of "information and communication competence" is not limited to technological or digital spheres only, on the contrary, it is transformed in a wider context and applied in almost all spheres of an individual's life. In the context of digitalization of the education system, it is assured that the possession of digital competence aims at purposeful and independent use of ICT tools in educational activities, as well as in the process of methodical and research work; maximum use of the potential of digital technologies in the process of identifying and solving pedagogical tasks. The experience of formation of digital competence of future masters of primary education within their professional training at PNU is presented n the article.